Global Transcriptomic Analysis of the Canine corpus luteum (CL) During the First Half of Diestrus and Changes Induced by in vivo Inhibition of Prostaglandin Synthase 2 (PTGS2/COX2) - Tavares Pereira, Miguel; Graubner, Felix R.; Rehrauer, Hubert; Janowski, Tomasz; Hoffmann, Bernd; Boos, Alois; Kowalewski, Mariusz P. (Frontiers in Endocrinology, 2019)
The canine luteal phase exhibits several peculiarities compared with other species. In early diestrus, the corpus luteum (CL) is, at least in part, independent of gonadotropins, and prostaglandins (PGs) appear to be among its main regulators. This was also observed with the inhibition in vivo of COX2, when also transcriptional capacity, vascularization and immune-related factors were affected. Here, we aimed to further investigate the potential effects of PGs withdrawal on the CL transcriptome by performing deep RNA sequencing (RNA-Seq). Samples from a previous in vivo study were used; bitches were treated for 5, 10, 20 or 30 days after ovulation with firocoxib (Previcox®), a PTGS2/COX2 inhibitor, or a placebo. Analysis of results was performed with SUSHI (framework from FGCZ) and with pathways and functional networks analyzers. Time-dependent effects were also investigated and used for quality control. More highly represented differentially expressed genes (DEGs, P<0.01, FDR<0.1) in the early CL (days 5 and 10) referred to proliferation and immune system, while in the mature CL (days 20 and 30) they were related with steroidogenesis. The absence of genes concomitantly affected by the treatment at all time-points suggested stage-dependency in the observed effects. Little effect was observed on days 5 and 10. Day 20 had the highest number of DEGs (n=1741), related with increased immune response. On day 30, DEGs found (n=552) referred to decreased steroidogenesis and vascularization. Our results suggest the presence of strong compensatory effects in the early CL and multidirectional effects towards gonadotropin-dependency of the CL after COX2 inhibition.